Norms of the Criminal Code of the Republic of Belarus on responsibility for illegal migration: formation, development and further perfection - Bakhur, Oleg I. (Journal of the Belarusian State University. Law, 2020)
A retrospective analysis of the development of norms on criminal responsibility for illegal migration in the Republic of Belarus in the context of the socio-economic transformation, that took place at the turn of the 20st–21st centuries, is given. It is noted that the criminalization of illegal migration and its organization made it possible to solve the urgent task of protecting public relations in the field of migration in the new conditions of freedom and the intensive development of international relations. Recommendations on the qualification of socially dangerous acts that infringe upon the established procedure for migration, as well as specific proposals to improve the rules on criminal responsibility for illegal migration, are formulated. The presented conclusions and measures will allow to achieve a correct identical interpretation and application of the analyzed criminal law norms, as well as to increase the effectiveness of countering illegal migration in the Republic of Belarus.